STRATEGIES IN SIMULTANEOUS INTERPRETING - Shokirov Manuchekhr Shamsidinovich (TADQIQOTLAR, 2025)
Abstract: Simultaneous interpreting involves listening to a speaker in one language and interpreting their words into another language in real-time. This demanding task requires the interpreter to process information rapidly while simultaneously speaking, making it one of the most challenging forms of language translation. Here are some examples of cognitive demands in simultaneous interpreting: